Estimating the technology of cognitive and noncognitive skill formation - Flavio Cunha; James Joseph Heckman; Susanne Schennach (Institute for the Study of Labor (IZA), 2010)
This paper formulates and estimates multistage production functions for children's cognitive and noncognitive skills. Skills are determined by parental environments and investments at different stages of childhood. We estimate the elasticity of substitution between investments in one period and stocks of skills in that period to assess the benefits of early investment in children compared to later remediation. We establish nonparametric identification of a general class of production technologies based on nonlinear factor models with endogenous inputs. A by-product of our approach is a framework for evaluating childhood and schooling interventions that does not rely on arbitrarily scaled test scores as outputs and recognizes the differential effects of the same bundle of skills in different tasks. Using the estimated technology, we determine optimal targeting of interventions to children with different parental and personal birth endowments. Substitutability decreases in later stages of the life cycle in the production of cognitive skills. It increases slightly in later stages of the life cycle in the production of noncognitive skills. This finding has important implications for the design of policies that target the disadvantaged. For some configurations of disadvantage and for some outcomes, it is optimal to invest relatively more in the later stages of childhood than in earlier stages.
Keywords: C31; J13; 330; Cognitive skills; noncognitive skills; dynamic factor analysis; endogeneity of inputs; anchoring test scores; parental influence; Kognitive Fähigkeiten; Bildungsniveau; Kinder; Bildungsinvestition; Eltern; Familiensoziologie; Faktorenanalyse; Schätztheorie; Statistischer Test; Theorie; Schätzung; USA